Case Study of Improving Reading and Writing Literacy Skills of Grade 2 Students - Naila Farikhatun Umamah; Fina Fakhriyah; Denni Agung Santoso (Universitas Negeri Semarang, 2025)
The purpose of this study is to describe the teacher's strategies applied in improving the literacy skills of second-grade students of Muhammadiyah Birrul Walidain Elementary School, Kudus. Literacy is a comprehensive ability that aims for students to understand various fields and apply knowledge in everyday life. This study uses a qualitative method with a case study approach. The research subjects were second-grade teachers and second-grade students of Muhammadiyah Birrul Walidain Elementary School, Kudus. Research data were obtained using observation, interviews and documentation techniques. The validity of the data in this study used several triangulation tests including source triangulation, technical triangulation and theory triangulation. Data analysis used an integrative model with the stages of data reduction, data presentation, drawing conclusions. The results of the study are divided into three stages of strategy, namely from the habituation stage there are four strategies that aim to get used to reading and writing, the development stage there are three strategies that aim to develop students' literacy skills, the learning stage there are three strategies that aim to always be interactive in the learning process through several interesting activities.